The law of the right to prior consultation (29785) and the protection of the rights of indigenous or native peoples 2013 - Salcedo Zeballos, Pamela Silvana (2017)
The present research was conducted in order to determine whether the Law on the Right to Prior Consultation (29785) protects the right of Indigenous Peoples or Native established by the International Convention OIT.Para 169 it was established following hypothesis: The Law of the Right to Prior Consultation ( 29785 ) careful and limited to the Law of Indigenous or Native Peoples established by the International Convention 169 .The research is a form of applied research, it is focused on the application of knowledge to the solution of a problem, as the theory confronts reality. It is also a type of Socio Legal Research that examines the events and social relations regulated by legal norms and that is to determine whether the Law on the Right to Prior Consultation (29785) protects the right of Indigenous Peoples or Native established in the International 169 such purpose OIT.Para considered information obtained through the application of the questionnaire, and the Certificate of Interview, as instruments for measuring the study variables. The data were tabulated and analyzed using tables and graphs. After the phase of analysis and interpretation of the results was tested the hypothesis of our research.